POTENTIAL TESTING OF WASTE SKIN ONION (Allium ascalonicum) AS A LARVACIDE AGAINST THE DEATH OF MOSQUITO LARVAS Culex sp - Rahmayanti Rahmayanti; Siti Hadijah; Fitriana Fitriana (Universitas Islam Negeri Ar-Raniry, 2022)
Diseases caused by mosquitoes continue to be the leading cause of illness and death worldwide. Malaria, filariasis, Japanese encephalitis and dengue fever are diseases that are clearly transmitted by mosquitoes of the genera Anopheles, Culex and Aedes. In addition, mosquitoes in the Culex genus have also been identified as the main vectors that transmit WNV (West Nile Virus) in several countries. One of the efforts to eradicate mosquitoes is to break the chain of mosquito distribution by eradicating mosquito nests and killing mosquito larvae. The use of abate insecticides as larvicides can be the most common way of controlling the growth of mosquito vectors. The use of abate for a long time will cause resistance or the larvae will be immune to abate (insecticide). Shallot skin has the potential to be developed as a biolarvicide for Culex sp mosquito larvae due to its phytochemical compounds. Onion peel waste was proven positive for containing alkaloids, saponins, flavonoids and tannins. The purpose of this study was to determine the effective concentration of onion peel waste powder (Allium ascalonicum) and the effective LC50 of onion peel waste powder (Allium ascalonicum) as larvicides against the death of Culex sp mosquito larvae at an effective powder concentration of 0.025 gr/ml, 0.05 gr. /ml, 0.075 gr/ml and 0.1 gr/ml. This type of research is an experimental laboratory, carried out from August to September 2021 at the Microbiology Laboratory of D III Study Program Medical Laboratory Technology, Health Poltekkes, Aceh Ministry of Health. The sample of this study was 325 larvae of Culex sp Instar III mosquito larvae. The treatments consisted of 4 effective concentrations of onion peel powder 0.025 g/ml, 0.05 g/ml, 0.075 g/ml and 0.1 g/ml and a negative control (Water) with 3 repetitions. Each treatment group contained 25 larvae. The data obtained were analyzed using the formula for the percentage of mortality of Culex sp larvae and the Probit analysis test to calculate the LC50. The results showed that the average larval mortality at a concentration of 0.025 gr/ml was 8 birds (32%), a concentration of 0.05 gr/ml was 9 birds (37%), a concentration of 0.075 gr/ml was 11 (44%), and the concentration of 0.1 g/ml is 16 animals (64%). While the negative control did not show death. And the LC50 value at 24 hours after treatment from the concentration of onion peel powder was 0.075%. Based on the results of the study, it can be concluded that onion peel powder (Allium ascalonicum) has the potential as a natural larvicide against the mortality of Culex sp larvae with LC50 obtained at an effective concentration of 0.075% powder. Keywords: Onion peel powder, Larvicide, Culex sp